The House of David: between political formation and literary revision - Leonard-Fleckman, Mahri (Fortress Press, 2016)
Pt. I. The Syrian House of X: 1. Ancient Syria and the "House of X" pattern -- 2. Adini, Halupe, and Zamani -- 3. Agusi and Bahiani -- pt. II. The Biblical House of David: 4. Rebellions against David -- 5. David, King of Israel (2 Samuel 2:1-5:3) -- 6. The assembly at Shechem (1 Kings 12:1-20) -- 7. The House of David in history